An Application of PSV-S in Fast Development of a Real-Time DSP System - Armein Z.R. Langi (Journal of ICT Research and Applications, 2016)
Virtual prototyping is natural in developing digital signal processing (DSP) systems using a product-service-value system (PSV-S) approach. Our DSP virtual prototyping approach consists of four development phases: (1) a generic DSP system, (2) a functional DSP system, (3) an architectural DSP system, and (4) a real-time DSP system. Such an approach results in a more comprehensive approach in the DSP system development. This paper shows an example of prototyping a voice codec on a single-chip DSP processor.